New campus-University Center-0001
Popular Informal Rendezvous is the student association-managed cafeteria with seating accommodations for more than 400. Special dining and committee rooms augment the main area where warm meals and mid-day snacks are available. An addition to the cafeteria will be constructed to increase seating facilities to about 700. Diners view the green expanse of the new campus through the glass enclosed front of the comfortable structure.